Synthesis, growth, spectral, optical and theoretical calculations of an organic crystal: 8-hydroxyquinolinium salicylate. (16th April 2019) - Prabha, D.; Sathyanarayanamoorthi, V.
Abstract: Single crystals of 8-hydroxyquinoline salicylate were grown by slow evaporation solution growth technique using methanol as a solvent at room temperature. The grown crystals were subjected to Powder XRD, FT-IR, UV–vis-NIR, Vickers test and photoconductivity studies. Powder XRD study reveals the crystalline nature of the grown crystal. FT-IR studies were performed for identifying the vibrational and confirm the presence of the various functional groups. The UV–vis-NIR spectrum was recorded in the range 200–800 nm regions was found to be a good for non-linear applications. The mechanical properties of the grown crystals have been analyzed by Vickers hardness test. Photoconductivity studies were carried out and the crystal reveals the positive photoconductivity in nature. In addition to that, the quantum chemical calculations on 8HQSA have been performed by density functional theory.